PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA KARTU KUNING (AK I) PADA DINAS TENAGA KERJA KOTA SAMARINDA - Heriyanto, Susi Oktaviani Robin Jonathan, (EKONOMIA, 2018)
This study aims to determine the reliability, responsiveness, assurance, empathy, and physical evidence affect the satisfaction of yellow card users (AK.I) job seekers in the Department of Labor Samarinda City.Research population used by researchers is all the yellow card maker at the Office of Manpower of Samarinda City. The sample was 98 respondents with slovin formula and sample selection using simple random sampling technique. Data analysis techniques use multiple linear regression analysis with classical assumption test and hypothesis testing.The results concluded that: 1) reliability has significant effect on satisfaction, it can be seen from t arithmetic for reliability variable equal to 3,207> 1,986. 2) responsiveness has a significant effect on satisfaction, it can be seen from t arithmetic for the variable of responsiveness of 4,709> 1,986, 3) the guarantee has a significant effect on satisfaction, it can be seen from t arithmetic for guarantee variable equal to 2,935> 1,986. 4) empathy has a significant effect on satisfaction, it can be seen from t arithmetic for empathy variable of 2,450> 1,986. 5) physical evidence has a significant effect on satisfaction, it can be seen from t arithmetic for physical evidence variables of 5,212> 1,986,6) quality of reliability, responsiveness, assurance, empathy and physical evidence simultaneously have a significant positive effect on satisfaction, it can seen from f arithmetic equal to 18,550> 2,31.